2010
DOI: 10.1166/jnn.2010.2462
|View full text |Cite
|
Sign up to set email alerts
|

NIR Femtosecond Laser Induced Hyper-Rayleigh Scattering and Luminescence from Silver Nanoprisms

Abstract: The nonlinear response of silver nanoprisms (edge length 40 +/- 5 nm and thickness 4.5 +/- 0.5 nm) was studied by exciting with NIR femtosecond pulses (780-880 nm). These nanostructures were observed to generate hyper-Rayleigh scattering (HRS) and broadband luminescence. While HRS showed the expected second order power dependence, the luminescence was observed to follow a third order excitation power dependence. Both HRS and luminescence were observed to be dipolar in nature. The first hyperpolarizability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(49 reference statements)
0
3
0
1
Order By: Relevance
“…These nanoparticles are noncentrosymmetric due to their intrinsic threefold symmetry. First hyperpolarizabilities have already been reported , but here, we wish to discuss the signal contribution of shape noncentrosymmetry versus size retardation from an experimental point of view as this has not been performed before. In addition, the question of the presence of nanospheres in non-negligible amounts among the nanoprisms must be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…These nanoparticles are noncentrosymmetric due to their intrinsic threefold symmetry. First hyperpolarizabilities have already been reported , but here, we wish to discuss the signal contribution of shape noncentrosymmetry versus size retardation from an experimental point of view as this has not been performed before. In addition, the question of the presence of nanospheres in non-negligible amounts among the nanoprisms must be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have reported single particle studies on Ag triangular nanoprisms. ,,,, They have primarily focused on the LSPR position of the scattering or the absorption spectra. , Other studies have focused on fluorescence, luminescence, and higher order multipole plasmons . The effect of tip truncation on Ag nanoprisms was investigated by Sherry et al, who showed that nanoprisms with sharper tips had a red-shifted λ max compared to nanoprisms with more truncated tips.…”
Section: Introductionmentioning
confidence: 99%
“…But there are very few reports on the determination of β values for nano-triangles in solution. Silver nanoparticles [50][51] display very high nonlinear responses. On the contrary, the hyperpolarizabilities of gold nanoprisms as reported in Ref.…”
Section: Introductionmentioning
confidence: 99%